NILAI-NILAI MODERASI DALAM BUKU AJAR SEJARAH KEBUDAYAAN ISLAM KELAS X MADRASAH ALIYAH - Abbas, Ngatmin; Fathurrohman, Mukhlis; Intan Apriliani, Elina (CV. Kalimasada Group, 2024)
This study aims to analyze the values of moderation education contained in the teaching books of Islamic Culture History Class X for Madrasah Aliyah. The research method used is content analysis with a qualitative approach. Research data is collected through observations and documentation on material related to moderation education. The results show that the textbook contains some of the values of moderation, such as tolerance, justice, discretion, and balance. Implications of these findings are the importance of moderation education in shaping moderate attitudes and behavior in students. Therefore, the textbook of Islamic Culture History of Class X Madrasah Aliyah can be an effective resource in introducing and reinforcing the values of Moderation to students.